Evaluasi Kinerja Daerah Irigasi Jragung Kabupaten Demak - Putri, Eka Wulandari Srihadi; Harisuseno, Donny; Purwati, Endang (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2015)
Jragung irrigation Area is located in Demak Regency has decreasedin its performance. The result of existing analysis showed that there is an imbalance of irrigation water within it. Based on its performance analysis taken from regulation of the ministry of public works No. 32/PRT/M/2007, Jragung Irrigation area has been classified as poor and requiremore attention with 66.95% working performance only. Efforts to increase its performance is by rehabilitation priority scale with following the AHP (Analytical Hierarcy Process) methods. With its main priority is Jragung Dam and Main Canal of Jragung, subsequently Teluk Secondary Canal, Sugihwaras Secondary Canal, Jragung Secondary Canal, Karangsono Secondary Canal, Ngumpul Secondary Canal, Pamongan Secondary Canal and Panjen Secondary Canal respectively. Efforts to overcome the imbalance of irrigation water is by the alteration of cropping periods from November to December and conventional cropping methods to SRI (System Rice Intensification) methods could save 53.25 % of irrigation water. Keywords : Irrigation Performance, Water Balance, AHP, Priority Scale, SRI Method